The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/qua.22321
|View full text |Cite
|
Sign up to set email alerts
|

MP2 and DFT study of IR spectra of TCNE‐methylsubstituted benzene complexes: Is charge transfer important?

Abstract: ABSTRACT:The second-order Møller-Plesset (MP2) and density functional theory (DFT; B3LYP, B3LYP-D) approaches show that the CN (and also CAC) stretching IR vibrations are relatively small but reproducibly shifted to lower frequencies in a series of methylbenzenes-tetracyanoethylene (NMB-TCNE, N ϭ mono-, di-, …, hexa-) complexes with increasing number of methyl groups (N). These CN stretching IR frequency shifts, ranging from 8 to 12 cm Ϫ1 , are linearly dependent on number N but still 2-4 times greater than re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The interplanar distances (R DA ) and the ground-state dipole moments (μ DA ) are very similar for both conformers (see Table 4). These results agree in general with a few previous computational studies of the BZ−TCNE complex, [65][66][67][68]92 except that the interplanar distance calculated here is somewhat shorter. 68 Very recently, Kuchenbecker and Jansen 67 reported high-level ab initio calculations on the BZ−TCNE complex.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…The interplanar distances (R DA ) and the ground-state dipole moments (μ DA ) are very similar for both conformers (see Table 4). These results agree in general with a few previous computational studies of the BZ−TCNE complex, [65][66][67][68]92 except that the interplanar distance calculated here is somewhat shorter. 68 Very recently, Kuchenbecker and Jansen 67 reported high-level ab initio calculations on the BZ−TCNE complex.…”
Section: Methodssupporting
confidence: 93%
“…The system of interest here is the EDA complex containing benzenes (BZ) as the donor and tetracyanoethylene (TCNE) as the acceptor. The series of EDA complexes containing TCNE and various methyl-substituted benzenes (MBZ) are among the earliest examples of EDA complexes ,, and have been studied extensively. ,, Among all MBZ–TCNE complexes, hexamethylbenzene–TCNE (HMB–TCNE) is probably the most intensively studied system both experiemntally , and theoretically. , Surprisingly, compared with HMB–TCNE, the smallest member of the series, namely, the BZ–TCNE complex, has not been given much attention. Early studies of the BZ–TCNE complex in the vapor and liquid phases have focused on the thermodynamic properties. ,, To the best of our knowledge, the only available time-resolved data for BZ–TCNE is a transient-absorption study that reported a CR rate of 1.4 × 10 10 s –1 in dichloromethane .…”
Section: Introductionmentioning
confidence: 99%
“…The series of EDA complexes containing tetracyanoethylene (TCNE) as the acceptor and methyl-substituted benzenes (MBZ) as the donor have been widely studied as model sytems. , Among them, hexamethylbenzene-TCNE (HMB-TCNE) is probably the most intensively studied MBZ-TCNE system both experimentally and theoretically. , Surprisingly, the smallest member of the series, namely the benzene-TCNE (BZ-TCNE) complex, has not been given much attention. Recently, we have studied the ultrafast CT-state relaxation dynamics of the BZ-TCNE complex in solvents of different polarities with ultrafast broadband time-resolved fluorescence (TRFL) spectroscopy .…”
Section: Introductionmentioning
confidence: 99%